Outpatient Loyalty and Its Determinants: The Roles of Service Quality, Hospital Image, Trust, and Digital Promotion at M.M. Dunda Limboto Hospital - Suyanto, Mohamad Afan; Karundeng, Deby Rita; Yakup, Anggita Permata; Dera, Firman; Yasin, Rahmi Novi (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
In recent years, patient loyalty has gained increasing attention as hospitals face growing competition and rising patient expectations, particularly in outpatient services where first impressions are formed. This study explores how service quality, hospital image, trust, and digital promotion influence outpatient loyalty at M.M. Dunda Limboto Hospital. The research focuses on outpatient care, considering its strategic role in shaping patients’ decisions to return and recommend hospital services. A quantitative research design was adopted, using survey data collected from outpatients through structured questionnaires. The data were analyzed using multiple linear regression to assess both individual and combined effects of the explanatory variables on patient loyalty. The results reveal that service quality, hospital image, trust, and digital promotion each have a positive and statistically significant effect on outpatient loyalty. When examined simultaneously, these factors jointly exert a strong influence, indicating that patient loyalty is not driven by a single aspect of service, but rather by the overall experience created through consistent service delivery, credible institutional reputation, and effective communication. Notably, digital promotion emerges as the most influential variable, reflecting the growing role of digital platforms in shaping patient perceptions and engagement. These findings suggest that hospital management should view loyalty as a long-term outcome of integrated service quality improvement, trust-building practices, and meaningful digital interaction with patients.